Ang dako nga balay sang manga Gaston the balay Negrense's role in the construction and validation of Negrense identity. - De la Cruz, Gellie Jill P.
This paper sseeks to identify and analyze the cultural identity within the Balay Negrense's exhibits and narratives. Through collaboration between the Negros Cultural Foundation, Inc., and the Gaston Family, the Balay Negrense became the first museum on the island of Negros, and it serves to present the lifestyle of Negrenses during their socio-economic peak under Spanish occupation. The exhibits within the Balay Negrense evoke the opulent lifestyle of the Gaston family, which materialized through their forefather, Yves Gaston's primary involvement in the industrialization of the sugar industry in Negros. Though some scholars have already tackled the question of how museums and their exhibits can be associated with group identity, this is the first study that deals with a museum's construction and validation of a locality's cultural identity utilizing a postcolonial lens. Through qualitative interviews with Negrenses from various socio-economic strata and going on multiple tours to investigate the exhibits and narratives within the museum, this paper reveals that the Balay Negrense's curation tends to display exhibits that exude high culture and focus their narratives on the lifestyle of the Gaston family and other local elites. These exhibited artifacts celebrate the status symbols that the local elites utilized as simulacra of the colonizers' identity in response to Spanish imperialism, and the lifestyle presented signifies the persistent visibility of the local elites in the collective memory of the Negrenses. Finally, the museum's preservation of a lifestyle during the Golden Age of Negros legitimizes the Balay Negrense's role as a culturally regenerative institution. Key terms: museum, sugar industry, identity, high culture, cultural regeneration